Pedagogical professional improvement and the ability formación to search for information - Sandra Williams Serrano; Luis Alberto Mass Sosa; José Aurelio Díaz Quiñones; Yudith Brito Pérez de Corcho; Ania Bernal Consuegra (Medisur)
The current development of science and technology constitutes a challenge for medical universities, as training centers in order to guarantee a graduate capable of managing the necessary knowledge to fulfill their social mission. An adequate ability to search for information is required, which allows for proper knowledge management and better teaching results; but the teaching staff must plan strategic actions with a view to achieving the formation of this research skill. Actions are suggested to work on the formation of the aforementioned skill, based on workshops that address the essentials for its operationalization through the contents that are taught; and tax the execution of student research. The search for information not only provides tools for the development of research, but also constitutes an instrument to promote logical thinking skills, with a high impact when the student, independently, faces larger tasks, for which it is suggested develop a system of workshops for teacher preparation.